Visual Java Builder a Java GUI designer - Baldos, Christina G.; Go, Jan Michael Vincent M. (2007)
Visual Java Builder is an easy-to-use visual Java GUI Builder for Java Swing applications. The main objective of this project is to provide an application GUI solution for Java developers. The Visual Java Builder enables Java developers to create sophisticated GUI applications. It helps design the GUI of a Java application visually by dragging controls onto a design-time representation of the application. Java, an object-oriented programming language, is now becoming popular. Software applications of today rely heavily on its user interface. In Java, each user control of GUI component must be coded manually along with its properties. For huge projects, designing the interface could take as much time as that spent on analyzing and working on the "real tasks". To save the developer from spending too much time because of this tedious manual coding, a programming tool that will generate files for the user interface will be the most useful.